The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.18130/v3kc0c
|View full text |Cite
|
Sign up to set email alerts
|

Regional Mechanics of Demand Ischemia During Cardiac Stress Testing

Abstract: Currently, the most effective non-invasive method for early diagnosis of coronary artery disease is the cardiac stress test. In this test, stress is induced by treadmill exercise or with a pharmacologic agent such as dobutamine, and myocardium with insufficient coronary flow reserve, usually caused by coronary stenosis, experiences an imbalance between oxygen supply and demand known as demand ischemia. This causes altered mechanical and electrical behavior that is often identified using cardiac imaging. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 134 publications
(274 reference statements)
0
4
0
Order By: Relevance
“…have shown that the standard deviation of volumes computed from segmentation of RT3D images by different observers is 8% of the mean end‐diastolic volume (EDV) and 13% of the mean end‐systolic volume (ESV). Using data from our previously published study of supply ischemia in a canine model, we similarly found relative standard deviations across 5 observers of 9% for EDV and 12% for ESV . Regional wall‐motion analysis is more susceptible to small, local segmentation errors that tend to cancel out in volume calculations.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…have shown that the standard deviation of volumes computed from segmentation of RT3D images by different observers is 8% of the mean end‐diastolic volume (EDV) and 13% of the mean end‐systolic volume (ESV). Using data from our previously published study of supply ischemia in a canine model, we similarly found relative standard deviations across 5 observers of 9% for EDV and 12% for ESV . Regional wall‐motion analysis is more susceptible to small, local segmentation errors that tend to cancel out in volume calculations.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, we found a somewhat higher variability of AAFs computed from the same segmentations: the standard deviation of AAF across the 5 observers was 6% of the endocardial surface for a group of occlusions with an average size of 25%. However, the average error in AAF compared to ischemic region sized assessed by microspheres ranged from 2 ± 12% to 8 ± 13% for the 5 observers, compared to 14% and 19% for visual assessment of the number of segments affected . These results suggest that user‐assisted segmentation using current commercial software is sufficient to yield consistent, accurate estimates of ischemic region size from ∆3DFS.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations